ANALISIS KELAYAKAN USAHA HIDROPONIK BAWANG MERAH PADA UMK FRESH HIDROPONIK DI KECAMATAN KEDAMEAN KABUPATEN GRESIK - administrator, administrator; Dianto, Aris Agus; Susanto, Heri (Fakultas Pertanian Universitas Wijaya Putra, 2023)
This study aims to determine the feasibility of a hydroponic business for Small andMedium Enterprises (SMEs) using the Break Even Point (BEP) approach. The population inthis study are agricultural entrepreneurs who use a hydroponic system in cultivating plants,namely UKM Fresh Hydroponics. The selection of this location was based on purposivesampling based on the length of time the business had been running because FreshHydroponics was the pioneer of hydroponic vegetable farming in Kedamean District. Thisresearch was conducted in January 2022 in Gresik, East Java. The data collection techniquesused were literature searches, observations and interviews. The data used is primary data frominterviews with Ms. Sutik. as the person in charge of UKM Fresh Hydroponics. The findings inthis study indicate that the Fresh Hydroponics business in hydroponic vegetable cultivationuses a small-scale Nutrient Film Technique (NFT) system with the types of plants planted,namely caisim mustard and shallots. The results of the calculation of the red onion R/c ratio >1 one, namely 1.337449228, it can be said that the shallot business is feasible to run with atotal production exceeding the BEP of 35 kg, a price level that exceeds the price BEP of IDR28,000.00/kg in January, and revenue which exceeds the revenue BEP of IDR 980,000.00